Florida Pest Management Industry Economic Contributions Report - Hayk Khachatryan; Xuan Wei; Christa D. Court (EDIS)
Florida's pest management industry is one of the nation’s leaders, accounting for more than 14 percent of pest management establishments in 2021. Among other services, this industry provides insect extermination and control, bedbug extermination, mosquito control, termite extermination and control, and rodent control and extermination. The market share concentration of the Florida pest management industry has increased due to consolidation during the past decade, but the general concentration within the industry has remained relatively low. Most operators are midsize or small and strategically located near densely populated areas. To estimate economic contributions of the Florida pest management industry for the most recent fiscal year, we sent survey questionnaires to more than 3,500 pest control firms and received responses from 764 of them. We then conducted an economic contribution analysis using the IMPLAN© regional economic modeling system and associated databases.